Review of media coverage on refugee crises: the case of Vietnamese Boat People (VBP) in Bidong Island / Azlinawati Ngainon ...[et al.] - Ngainon, Azlinawati; Md. Redzuan, Ahmad; Khamis, Mohd Fadly; Jamaluddin, Mohd Farizi (Centre For Media And Information Warfare Studies, 2021)
The Vietnam War was fought between the communist government of North Vietnam and the government of South Vietnam. Ho Chi Minh declared independence from France when the French surrendered and announced a cease-fire. When Vietnam was split at the 17th parallel, the Democratic Republic of Vietnam (North Vietnam) and the Republic of Vietnam were created (South Vietnam). Between the two limits, citizens were free to travel. Ngô nh Dim gave control to South Vietnam, whereas Ho Chi Minh gave power to North Vietnam. The Geneva Agreements were signed, and they declared that Vietnam would be unified through elections. However, Ngô nh Dim said that South Vietnam did not sign the accords and was not obliged by them. After failing to unite Vietnam through elections, North Vietnam decides to unite the country through force, igniting the Vietnam War. During the 1970s and 1980s, media coverage was minimal. Unlike now, when social media has become the most efficient means of disseminating information and informing global audiences about what is occurring in other nations. Media reporting ways easier and simplifies and has a significant impact on reporting process. The purpose of this study is to examine the scant information about Vietnamese Boat People given through the media throughout the conflict using newspaper reviews published between 1970 and 1985. The findings demonstrated the importance of the media's role in aiding and expediting conflict resolution.